Impact of adherence to procalcitonin antibiotic prescribing guideline recommendations for low procalcitonin levels on antibiotic use - Brian E. Malley; Jonathan G. Yabes; Elizabeth Gimbel; Chung-Chou H. Chang; Donald M. Yealy; Michael J. Fine; Derek C. Angus; David T. Huang; for the ProACT Investigators (BMC Infectious Diseases, 2023)
Abstract Background The Procalcitonin Antibiotic Consensus Trial (ProACT) found provision of a procalcitonin antibiotic prescribing guideline to hospital-based clinicians did not reduce antibiotic use. Possible reasons include clinician reluctance to follow the guideline, with an observed 64.8% adherence rate. In this study we sought to determine the threshold adherence rate for reduction in antibiotic use, and to explore opportunities to increase adherence. Methods This study is a retrospective analysis of ProACT data. ProACT randomized 1656 patients presenting to 14 U.S. hospitals with suspected lower respiratory tract infection to usual care or provision of procalcitonin assay results and an antibiotic prescribing guideline to the treating clinicians. We simulated varying adherence to guideline recommendations for low procalcitonin levels and determined which threshold adherence rate could have resulted in rejection of the null hypothesis of no difference between groups at alpha = 0.05. We also performed sensitivity analyses within specific clinical settings and grouped patients initially prescribed antibiotics despite low procalcitonin into low, medium, and high risk of illness severity or bacterial infection. Results Our primary outcome was number of antibiotic-days by day 30 using an intention-to-treat approach and a null hypothesis of no difference in antibiotic use. We determined that an 84% adherence rate in the hospital setting (emergency department and inpatient) for low procalcitonin could have allowed rejection of the null hypothesis (3.7 vs 4.3 antibiotic-days, p = 0.048). The threshold adherence rate was 76% for continued guideline adherence after discharge. Even 100% adherence in the emergency department alone failed to reduce antibiotic-days. Of the 218 patients prescribed antibiotics in the emergency department despite low procalcitonin, 153 (70.2%) were categorized as low or medium risk. Conclusions High adherence in the hospital setting to a procalcitonin antibiotic prescribing guideline is necessary to reduce antibiotic use in suspected lower respiratory tract infection. Continued guideline adherence after discharge and withholding of antibiotics in low and medium risk patients with low procalcitonin may offer impactful potential opportunities for antibiotic reduction. Trial registration Procalcitonin Antibiotic Consensus Trial (ProACT), ClinicalTrials.gov Identifier: NCT02130986. First posted May 6, 2014.